2023
DOI: 10.3390/ijms241310993
|View full text |Cite
|
Sign up to set email alerts
|

Serum 5-Methyltetrahydrofolate Status Is Associated with One-Carbon Metabolism-Related Metabolite Concentrations and Enzyme Activity Indicators in Young Women

Abstract: Maintaining optimal one-carbon metabolism (OCM) is essential for health and pregnancy. In this cross-sectional study, folate status was assessed based on 5-methyltetrahydrofolate (5-MTHF) levels, and the association between 5-MTHF and OCM-related metabolites was investigated in 227 female Japanese university students aged 18–25 years. The participants were divided into high and low 5-MTHF groups based on their folate status. Serum samples of the participants were collected while they were fasting, and 18 OCM-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 120 publications
3
7
0
Order By: Relevance
“…Continuous variables are presented as a median and interquartile range because of the skewed distribution of serum OCM-related metabolites. Consistent with our previous report [ 8 ], we used specific ratios as indicator of activity of the metabolic pathway (substrate to product concentration ratios): the betaine/DMG ratio for indicator of betaine–homocysteine methyltransferase (BHMT) pathway [ 21 ], the SAM/SAH ratio for indicator of methyltransferase pathway [ 22 ], and the tCys/tHcy ratio for indicator of the metabolic pathway in the transsulfuration pathway flux (cystathionine β-synthase and cystathionine γ-lyase) [ 23 ]. We also measured the cord blood/maternal blood metabolite ratio at birth, indicating the number of times the concentration of metabolites in cord blood corresponds to that in maternal blood at birth.…”
Section: Methodssupporting
confidence: 94%
See 4 more Smart Citations
“…Continuous variables are presented as a median and interquartile range because of the skewed distribution of serum OCM-related metabolites. Consistent with our previous report [ 8 ], we used specific ratios as indicator of activity of the metabolic pathway (substrate to product concentration ratios): the betaine/DMG ratio for indicator of betaine–homocysteine methyltransferase (BHMT) pathway [ 21 ], the SAM/SAH ratio for indicator of methyltransferase pathway [ 22 ], and the tCys/tHcy ratio for indicator of the metabolic pathway in the transsulfuration pathway flux (cystathionine β-synthase and cystathionine γ-lyase) [ 23 ]. We also measured the cord blood/maternal blood metabolite ratio at birth, indicating the number of times the concentration of metabolites in cord blood corresponds to that in maternal blood at birth.…”
Section: Methodssupporting
confidence: 94%
“…Furthermore, in our study, the betaine/DMG ratios were negatively correlated with tHcy levels in maternal and cord blood at all sampling periods, and these correlations strengthened with advancing gestational age ( Table 3 ). Previously, we reported that in nonpregnant young women, when serum 5-MTHF concentrations in young women were divided into high-and low-MTHF groups by median, the low 5-MTHF group showed a possible enhancement of betaine-mediated Hcy metabolism compared with the high 5-MTHF group [ 8 ]. As gestation progresses, maternal serum 5-MTHF levels decrease [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations